FACTORS ASSOCIATED WITH THE INCIDENCE OF LBW IN THE SERPONG 2 HEALTH CENTER WORK AREA, SOUTH TANGERANG CITY IN 2022 - Ummu Kulsum; Nurmalia Lusida; Ernyasih; Andriyani (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
A baby who weighs less than 2,500 grams at delivery is considered low birth weight. Since low birth weight affects 15% to 20% of all infants worldwide, or more than 20 million babies annually, it is regarded as a serious public health concern. It is the tenth most common low birth weight condition in Indonesia, with a prevalence rate of 9.97%. According to the findings of the 2021 Indonesian Nutrition Status Survey (SSGI), which is conducted at the district or city level, the country's low birth weight case rate has risen to 6.6%. Finding the factors linked to the occurrence of LBW in the Serpong 2 Health Center's Work Area in South Tangerang City in 2022 was the aim of this study. The chi-square test was used to analyze secondary data collected for this study from the 2022 Field Learning Experience of the Faculty of Public Health, University of Muhammadiyah Jakarta. With No.10.134.B/KEPK-FKMUMJ/VI/2023, the The Universitas Muhammadiyah Jakarta's, Faculty of Public Health's Health Research Ethics Committee granted ethical approval for this study. The findings indicated a strong correlation between the incidence of LBW and the prenatal care visits made by mothers. There is no significant correlation between the occurrence of LBW and maternal concerns, age, education, employment position, or parity.